If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3p + 2 = 2p + 12 Reorder the terms: 2 + -3p = 2p + 12 Reorder the terms: 2 + -3p = 12 + 2p Solving 2 + -3p = 12 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 2 + -3p + -2p = 12 + 2p + -2p Combine like terms: -3p + -2p = -5p 2 + -5p = 12 + 2p + -2p Combine like terms: 2p + -2p = 0 2 + -5p = 12 + 0 2 + -5p = 12 Add '-2' to each side of the equation. 2 + -2 + -5p = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -5p = 12 + -2 -5p = 12 + -2 Combine like terms: 12 + -2 = 10 -5p = 10 Divide each side by '-5'. p = -2 Simplifying p = -2
| 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 | | 3(9-8x)+8(3x+4)=11 | | 5x-2y+20=0 | | 10-(4x-5)=6-5x | | 4w-16=12+3w | | 5w-2(w-18)=7w-15 | | (x+1)/(x-3)-3/5=4/(x-3) | | 2d^2+12d/d+6 | | 4x+5=3(x+15) | | x(3x-2)+x(4x-5)=(7x+4)(x-1) | | x+1/x-3-3/5=4/x-3 | | 3.7x-1.9=-9.3 | | 12x-8+3x-4=11x-2+3x | | 5b-20=10b+5 | | (4x^2+6x-2)+(6x^2-9x+5)= | | x^4-16x^3+60x^2=0 | | 3=-5x+1 | | 15x-14=14x | | 5/x=7/8 | | 2x+4x+10=22 | | 6k+54-2+9k=14k | | x-6/x+2=5/6 | | 7x=10+5x | | 2x=1398 | | -3a+9+5a=7a-2a | | 6y-6=8+5y | | 1/4x+6=-9 | | 17x=136 |